Anishinabek Women’s Nibi Giikendaaswin (Water Knowledge) - Susan Chiblow (Ogamauh annag qwe) (Water, 2019)
This paper springs from conversations and my life experiences with Anishinabek Elders and practitioners, which includes my understanding of my life journey in re-searching for Anishinabe qwe (woman) giikendaaswin (knowledge, information, and the synthesis of our personal teachings). Anishinabek women have giikendaaswin about nibi (water) that can transform nibi (water) governance. Re-searching for giikendaaswin is directly linked to inclusive decision-making. This paper describes how Anishinabek understand and construct giikendaaswin based on Anishinabek ontology and epistemology, which includes nibi (water) giikendaaswin. This supports what Anishinabek know, how we come to know, how we know it to be true, and ultimately why we seek giikendaaswin.